RADIONUCLIDES CONCENTRATION IN THE MAIN KINDS OF FOODS & FOODSTUFFS IN SOME ECOLOGICAL REGIONS OF VIETNAM - NGUYEN , TRONG NGO; NGUYEN , THANH BINH; TRUONG , Y; NGUYEN , VAN PHUC; LE , NHU SIEU; NGUYEN , THI LINH; PHAN , SON HAI; NGUYEN , MONG SINH; LE , NGOC CHUNG (Nuclear Science and Technology, 2012)
To acquire the existence of natural and artificial radionuclides in the main kinds of foods & foodstuffs samples is a necessary task for assessing the environment impact. For this reason, the Ministry of Science and Technology had approved a project on “Investigation on radionuclides and toxic elements concentration in the main kinds of foods & foodstuffs of Vietnam”. The paper focused on: Concentration of 40K, 210Pb, 210Po, 226Ra, U, Th, 90Sr, 137Cs, 239, 240Pu radionuclides in foods & foodstuffs samples collected from the Southern of Vietnam (Lam Dong, Ninh Thuan, Tien Giang, Can Tho and Tra Vinh Provinces and Ho Chi Minh City). About 1250 data of above mentioned radionuclides concentrations in 140 the samples collected at 6 selected sites are summarized and presented in this paper. In general, the levels of radionuclides in the samples are much lower as compared with the ICRP's Guidline levels.